What’s the Function of Connexin 32 in the Peripheral Nervous System? - Bortolozzi, Mario (Frontiers in Molecular Neuroscience, 2018)
Connexin 32 (Cx32) is a fundamental protein in the peripheral nervous system (PNS) as its mutations cause the X-linked form of Charcot–Marie–Tooth disease (CMT1X), the second most common form of hereditary motor and sensory neuropathy and a demyelinating disease for which there is no effective therapy. Since mutations of the GJB1 gene encoding Cx32 were first reported in 1993, over 450 different mutations associated with CMT1X including missense, frameshift, deletion and non-sense ones have been identified. Despite the availability of a sizable number of studies focusing on normal and mutated Cx32 channel properties, the crucial role played by Cx32 in the PNS has not yet been elucidated, as well as the molecular pathogenesis of CMT1X. Is Cx32 fundamental during a particular phase of Schwann cell (SC) life? Are Cx32 paired (gap junction, GJ) channels in myelinated SCs important for peripheral nerve homeostasis? The attractive hypothesis that short coupling of adjacent myelin layers by Cx32 GJs is required for efficient diffusion of K+ and signaling molecules is still debated, while a growing body of evidence is supporting other possible functions of Cx32 in the PNS, mainly related to Cx32 unpaired channels (hemichannels), which could be involved in a purinergic-dependent pathway controlling myelination. Here we review the intriguing puzzle of findings about Cx32 function and dysfunction, discussing possible directions for future investigation.